Pengaruh Ekonomi Keluarga terhadap Motivasi Belajar Siswa Kelas IX SMP Negeri 2 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2019/2020 - Tianggur Medi Napitupulu (Institut Agama Kristen Negeri Tarutung, 2021)
Abstract:This study aims to determine the positive and significant influence of the family economy on the learning motivation of class IX students at SMP Negeri 2 Sipoholon, North Tapanuli Regency, for the 2019/2020 Academic Year. The population in this study amounted to 156 people. The research sample was 30% of the entire population, namely 47 people.. From the relationship test, it is known that rcount rtable or 0.289 0.823. This shows that there is a relationship between variable X and variable Y. From the significant correlation test, the value of tcount ttable (n-2) = (47-2) = 45 for = 0.05, namely 2.02 2.01, shows that there is a significant relationship between variable X and variable Y. Testing the regression equation Y over X obtained the regression equation Y =10.69+0.96 X. The magnitude of the influence of family economy on learning motivation of grade IX students of SMP Negeri 2 Sipoholon Tapanuli Regency North of the 2019/2020 school year is r2 x 100% = 0.0836 x 100% = 8.36%. While 91.64% is influenced by other factors. From the significant test, it was obtained that fcount ftable, namely 4.28 4.06. This means that the family economy has a positive and significant effect on the learning motivation of class IX students of SMP Negeri 2 Sipoholon, North Tapanuli Regency, for the 2019/2020 school year.Keywords: motivation to learn, family economic influence, the influence of family economy on learning motivation.Abstrak:Penelitian ini memiliki tujuan untuk mengetahui pengaruh positif dan signifikan ekonomi keluarga terhadap motivasi belajar siswa kelas IX SMP Negeri 2 Sipoholon Kabupaten Tapanuli Utara Tahun Ajaran 2019/2020. Populasi dalam penelitian ini berjumlah 156 orang. Sampel penelitian adalah 30% dari seluruh populasi yaitu 47 orang. Hal ini memperlihatkan bahwa terdapat hubungan antara variabel X dan variabel Y. Dari uji signifikan korelasi diperoleh nilai thitung ttabel (n-2) = (47-2) = 45 untuk α = 0,05 yaitu 2,02 2,01, menunjukkan bahwa terdapat hubungan yang signifikan antara variabel X dan variabel Y. Pengujian persamaan regresi Y atas X diperoleh persamaan regresi Besarnya pengaruh ekonomi keluarga terhadap motivasi belajar siswa kelas IX SMP Negeri 2 Sipoholon Kabupaten Tapanuli Utara tahun pelajaran 2019/2020 sebesar r2 x 100% = 0,0836 x 100%= 8,36 %. Sedangkan 91,64% dipengaruhi oleh faktor lain. Dari uji signifikan diperoleh fhitung ftabel yaitu 4,284,06. Artinya ekonomi keluarga berpengaruh positif dan signifikan terhadap motivasi belajar siswa kelas IX SMP Negeri 2 Sipoholon Kabupaten Tapanuli Utara tahun pelajaran 2019/2020.Kata kunci: motivasi belajar; pengaruh ekonomi keluarga, pengaruh ekonomi keluarga terhadap motivasi belajar.